PELAKSANAAN PERHITUNGAN, PEMOTONGAN, PENYETORAN, DAN PELAPORAN PAJAK PENGHASILAN PASAL 4 AYAT 2/FINAL ATAS TRANSAKSI PENJUALAN SAHAM DI BEI PADA PT. BOSOWA SEKURITAS ATAS NAMASIERLY SUGIANTO MASA PAJAK JULI SAMPAI DENGAN SEPTEMBER 2015 - Jiwa Pribadi Agustianto; Aji Prasetyo; Ricky Syah Putra (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2017)
This study discusses the 4 paragraph 2 / final income tax in the capital market sector, the implementation of the calculation, deduction, depositing and reporting of final PPh on the sale transaction of shares on the Indonesia Stock Exchange at PT.Bosowa Sekuritas on behalf of sierly sugianto. The author collects data by conducting interviews with the employees and customers concerned for stock sales transactions carried out every day during the exchange working hours and comparing them with regulations and laws that discuss the implementation. It turns out that the process of calculating, deducting, depositing and reporting the final PPh on the share sale transaction has been carried out by the Indonesia Stock Exchange, assisted by PT. Bosowa Securities, which runs well and in accordance with established regulations. Overall the process of implementing the calculation, deduction, depositing and reporting of final PPh on the sale of shares in the Indonesia Stock Exchange at PT.Bosowa Sekuritas is in accordance with applicable standards and laws in Indonesia, except that there is little negligence when storing data concerning stock sale transactions.